Quelle implication des destinataires de la norme ? La voie de la corégulation - Apolline Roger (VertigO)
Coregulation is hardly promoted by the European Community as a “good governance” tool. This analysis highlights how far the reality suits the discourse when coregulation is at stake.When coregulation is used as a substitute to classical regulation that the public authority does not want or can not adopt, it is likely that reality will be far from the theory. This coregulation raises legitimacy issues, and its environmental efficiency is doubtful. On the other hand, when used as a part of a policy mix including classical regulation, coregulation appears as an interesting method to increase participation and flexibility.